Acoustic Behaviour of Dysprosium Soaps in Methanol - UPADHYAY, S.K.; SHUKLA, R.K.; SHARMA, GOVIND (Asian Journal of Chemistry, 2010)
The studies of ultrasonic velocity in solutions of dysprosium butyrate and velerate soaps in methanol have been used to evaluate the various acoustic parameters. The result shows that ultarasonic velocity, molar sound velocity, density and specific acoustic impedence increases but adiabatic compressibility and intermolecular free length decreases with increasing soap concentration. The values of solvation number are almost constant for dilute solution but decreases rapidly above the critical micelle concentration (CMC) with increasing soap concentration. The apparent molal compressibility and apparent molal volume of dysprosium soap solution in methanol vary linearly below the CMC.